Safety Evaluation of Perforated String by Simulation Modeling and Mechanics Analysis Under Shock Loading - Dong Yang; Qiao Deng; Meng Yuan; Gang Cui; Dongyang Fan; Bo Jia (Applied Sciences)
The operating environment of perforated strings is highly complex, making their safety a critical concern, particularly when evaluating their performance under shock loading conditions. A simplified model of the perforated string system subjected to shock loading is developed, leading to the formulation of a shock load calculation model. This model is then used to analyze the relationship between peak pressure and axial force under shock loading. Based on field data and commercial software to verify the accuracy of the model, two wells in the Southwest region were evaluated for safety. The results show that, using this model, the peak pipe pressures under shock loading for the two wells are calculated to be 69.52 MPa and 82.93 MPa, respectively. When compared to results from a commercial software for analyzing wellbore dynamics, the error is minimal, suggesting that the model provides accurate calculations and predictions of peak pipe pressure within acceptable error margins. This model meets engineering requirements and can serve as a practical tool for safety evaluation. Overall, the findings demonstrate that the safety evaluation method and calculation model offer valuable guidance for engineering practice and provide a reliable reference for assessing the safety of perforated strings under shock loading conditions.